Application of an integrated ALES-GIS model in land suitability evaluation for tea cultivation in Di Linh - Bao Loc area - Ngọc, Hoàng Thị Huyền; Kỳ, Nguyễn Đình; Anh, Lưu Thế (Vietnam Journal of Earth Sciences, 2014)
Bao Loc - Di Linh area is located in the center of the South of Lam Dong province, which has a large and long-term tea cultivation area. However, the tea is grown spontaneously and the quality is unstable. The research was carried out to find out which is the suitable area that satisfy all the conditions for tea production planning, contributing to cultivation of high quality tea based on maximum exploitation of the advantages of the natural and human conditions in the study areas. The result of integrated ALES-GIS model application in land evaluation for cultivated tea show that, Bao Lam has 25.795,42 ha suitable for tea; Bao Loc has 10.130,78 ha and Di Linh has 12.809,08 ha. The study results have been also presented on the map at scale of 1:50.000. This research result is necessary for adjustment of land use planning for tea growth in Bao Lam, Bao Loc and Di Linh districts.